APLIKASI SECURE VIRTUAL OFFICE MENGGUNAKAN METODE AES, RSA, DAN MD5 - Jason Djatmiko; Lely Hiryanto; Bobby Tumbelaka (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
The developed application consists of three security features: MD5 hash that is used for login and registration purposes, RSA and AES encryption for uploaded files, and AES encryption for fetched e-mails which is performed before storing them to the database. The other features such as meetings management, task management, groups, discussion, etc. are designed to provide basic office functions to connected users. Each entry to the database is fully available to authorized administrators. Therefore, administrators will be able to maintain data if the need arises. Testing results show that the application has managed to withstand hacking attempts using SQL Injection. It also has been tested to process and secure user-inputted files and fetched e-mails. However, there is still a problem that arises whenever the user of the application tries to configure the mail client for Yahoo! Mail account. Key wordsAES, MD5, RSA, Secure Virtual Office.